Vulvar Tuberculosis—A Rare Manifestation of the Disease - Bragança, Cristina; Gonçalves, Inês; Guerreiro, Luísa; Janeiro, Maria (Revista Brasileira de Ginecologia e Obstetrícia / RBGO Gynecology and Obstetrics, 2019)
Tuberculosis is an infectious disease caused by Mycobacterium tuberculosis. According to data from the World Health Organization, this disease remains one of the leading causes of death worldwide. Although it most commonly affects the lungs, tuberculosis can compromise any organ. The present study reports a rare case of vulvar tuberculosis in a postmenopausal woman with a history of asymptomatic pulmonary and pleural tuberculosis, with no prior documented contact with the bacillus. Diagnosis was based on vulvar lesion biopsies, with histological findings suggestive of infection and isolation of M. tuberculosis by microbiological culture and polymerase chain reaction (PCR) essays. The lesions reverted to normal after tuberculostatic therapy.
Keywords: gynecology; vulvar diseases; tuberculosis